Republic of Tajikistan : Financial System Stability Assessment, including Reports on Observance of Standards and Codes on the following topics, Banking Supervision, and Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report ;, 2008)
The Republic of Tajikistan's Financial System Stability Assessment and reports on the Observance of Standards and Codes are examined. The Tajik financial system is small despite recent rapid growth. Overall, banks remain well capitalized and liquid, but the brisk expansion of their loan portfolios is rapidly eroding capital buffers in a context where governance and supervision of the financial system raise concerns. The governance, regulatory, and supervisory frameworks for the financial sector should be strengthened. The key areas for the banking sector include licensing, remedial actions, and disclosure of significant shareholders and beneficial ownership.